Pengembangan Modul Mikro Konseling Berbasis Psikospiritual untuk Meningkatkan Keterampilan Mahasiswa dalam Mengatasi Konflik Komunikasi Suami-Istri - Marimbun; Nengsih (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2026)
Marital communication conflict requires prospective counselors to combine core counseling skills with sensitivity to clients’ spiritual values. This study aimed to develop a psychospiritual-based micro-counseling module for students of Islamic Guidance and Counseling in managing marital communication conflict. Using a research and development design with the ADDIE model, participants included three expert validators, three practitioner/lecturer user validators, and 20 students in a limited readability and practice try-out. Data were collected through needs analysis, document review, expert validation, usability assessment, student responses, practice observation, and focus group discussion. Quantitative data were analyzed descriptively, while qualitative data were reduced, categorized, and used for module revision. The final module comprised six units: micro-counseling concepts, dynamics of marital communication conflict, psychospiritual techniques, micro-counseling skills, case-based practicum, and counselor self-evaluation. Expert validation scored 4.30 and usability testing 4.18, indicating high feasibility. The module is suitable for family counseling courses and micro-counseling practicum, though broader effectiveness testing is recommended.